B4C mineralizing role for mullite generation in Al2O3-SiO2 refractory castables. Issue 15 (15th October 2017) - Luz, A.P.; Gagliarde, J.H.; Aneziris, C.G.; Pandolfelli, V.C.
Abstract: Based on refractory end-users' requirements, continuous efforts have been made to design engineered products able to withstand high temperatures (800–1500 °C) and severe thermal gradients. One alternative to enhance the mechanical properties of alumina-based compositions consists of inducing in situ generation of phases with platelet or acicular shape within their matrix fraction, which may improve crack deflection and grain bridging mechanisms. Mullite and Al18 B4 O33 are some compounds that present such interesting features. Thus, this work addresses the evaluation of alumina refractory castables bonded with SioxX-Zero and/or microsilica, containing 0 or 1 wt% of B4 C (sintering additive), aiming to: (i) induce transient liquid sintering, (ii) point out which silica source could favor a more effective mullite formation at high temperatures, and (iii) analyze the influence of B4 C in the phase transformation and thermo-mechanical properties of the designed compositions. Comparing SioxX-Zero and microsilica-bonded refractories, the latter showed more likelihood to give rise to the mullite phase during the samples' thermal treatments. Moreover, adding B4 C to the castables containing 3 wt% of SiO2 induced the generation of a boron-rich liquid phase with transient features during the samples' firing step, favoring earlier sintering and faster mullite and Al18 B4 O33 formation. These transformations resulted in refractories with enhanced creep, thermal shock resistance and HMOR behavior in a broader temperature range (600–1550 °C), which may enable them to be used in various industrial applications (petrochemical, steel-making, etc.).